PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONBILITY DAN NILAI PERUSAHAAN TERHADAP PROFITABILITAS PERBANKAN SYARIAH YANG TERDAFTAR DI OTORITAS JASA KEUANGAN TAHUN 2012 – 2016 - Fadjar Harimurti, Handayani, Dewi Saptantinah Puji Astuti & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2018)
The Purpose of this Study is to analyze the effect of corporate social responbility and Firm value to profitability. The population of this study are all Islamic Banks registered in the Financial Services Authority. The sampling technique used in this study using non-random sample technique is using purposive sampling method with a sample of 6 Islamic banking. The analysis tool used in this study is multiple regression analysis. Analytical techniques in the form of statistical test F which shows whether all independent variables have a joint influence on the dependent variable and statistical test t which shows whether the partially independent variables have an influence on the dependent variable. The results of this study show that together (silmutan) disclosure of CSR and firm value have a significant influence on profitablitas company. Partially disclosure of CSR has a significant positive effect on profitability while firm value has no significant effect to profitability of company.Keywords: disclosure of CSR, firm value, profitability